Strengthening Participatory Oversight in the Stages of Simultaneous Regional Head Elections in Kampar Kiri Hulu District, Kampar Regency - Rony Jaya; Muslim; Mhd. Rafi; Muklis; Muhamad Rachmadi; Ahmad Riyanto (Society : Jurnal Pengabdian Masyarakat, 2026)
This community service activity aims to strengthen participatory oversight in the stages of the simultaneous regional head elections in Kampar Kiri Hulu District, Kampar Regency. The background of the activity stems from the need to encourage the implementation of participatory oversight that is adaptive to social, political, and cultural dynamics at the local level. This Community Service method is implemented using a Participatory Action Research (PAR) approach that positions the community as both the subject and agent of change through knowledge sharing, creating a space for dialogue, critical reflection, and collective action in strengthening participatory oversight of regional head elections in Kampar Kiri Hulu District, Kampar Regency, by involving a number of election supervisors throughout Kampar Kiri Hulu District. The results of the activity showed an increase in participants' understanding of the principles of supervision, as well as a growing awareness of the importance of cross-actor collaboration, especially between supervisors and civil society. The ongoing discussion resulted in understanding and awareness that enriched participants' insights in designing adaptive and contextual supervision strategies to encourage the formation of an inclusive participatory oversight culture in the simultaneous regional head elections in Kampar Kiri Hulu District, Kampar Regency in 2024.